Bidirectional two-sample Mendelian randomization study of causality between rheumatoid arthritis and myocardial infarction - Guo, Hao-Yang; Wang, Wei; Peng, Hui; Yuan, Hui (Frontiers in Immunology, 2022)
Background Epidemiological evidence suggests an association between rheumatoid arthritis (RA) and myocardial infarction (MI). However, causality remains uncertain. Therefore, this study aimed to explore the causal association between RA and MI. Methods Using publicly available genome-wide association study summary datasets, bidirectional two-sample Mendelian randomization (TSMR) was performed using inverse-variance weighted (IVW), weighted median, MR-Egger regression, simple mode, and weighted mode methods. Results The MR results for the causal effect of RA on MI (IVW, odds ratio [OR] = 1.041, 95% confidence interval [CI]: 1.007–1.076, P = 0.017; weighted median, OR = 1.027, 95% CI: 1.006–1.049, P = 0.012) supported a causal association between genetic susceptibility to RA and an increased risk of MI. MR results for the causal effect of MI on RA (IVW, OR = 1.012, 95% CI: 0.807–1.268, P = 0.921; weighted median, OR = 1.069, 95% CI: 0.855–1.338, P = 0.556) indicated that there was no causal association between genetic susceptibility to MI and an increased risk of RA. Conclusion Bidirectional TSMR analysis supports a causal association between genetic susceptibility to RA and an increased risk of MI but does not support a causal association between genetic susceptibility to MI and an increased risk of RA.